1997
DOI: 10.1017/s0022112097005375
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study of Mach reflection in steady flows

Abstract: The flow fields associated with Mach reflection wave configurations in steady flows are analysed, and an analytical model for predicting the wave configurations is proposed. It is found that provided the flow field is free of far-field downstream influences, the Mach stem heights are solely determined by the set-up geometry for given incoming-flow Mach numbers. It is shown that the point at which the Mach stem height equals zero is exactly at the von Neumann transition. For some parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 0 publications
11
114
0
Order By: Relevance
“…The inviscid flow conditions that result in either an RR or an MR as well as the transition between the two have been widely studied (Henderson 1967;Hornung, Oertel & Sandeman 1979;Hornung & Robinson 1982;Chpoun et al 1995;Vuillon, Zeitoun & Ben-Dor 1995;Li & Ben-Dor 1997;Ben-Dor 2007).…”
Section: Inviscid Transition Criteriamentioning
confidence: 99%
“…The inviscid flow conditions that result in either an RR or an MR as well as the transition between the two have been widely studied (Henderson 1967;Hornung, Oertel & Sandeman 1979;Hornung & Robinson 1982;Chpoun et al 1995;Vuillon, Zeitoun & Ben-Dor 1995;Li & Ben-Dor 1997;Ben-Dor 2007).…”
Section: Inviscid Transition Criteriamentioning
confidence: 99%
“…In an inviscid framework, it can be shown that m + decreases as g + increases, see e.g. Li & Ben-Dor (1997), provided that all other variables are held constant. Since the flow topology must fit well within the computational domain, g + was set to 5/4, which results in a relatively small Mach stem.…”
Section: Test Case Definitionmentioning
confidence: 99%
“…Finally, the MS height is defined by the relation between the inlet and throat cross sectional areas of the nozzle. RTO-TR-AVT-007-V3 The phenomenon of regular and irregular shock reflections has been the subject of numerous investigations [19][20][21][22][23][24]. For a given Mach number and ratio of specific heats, only regular Reflections (RR) are possible for shock angles where the pressure rise across the primary and secondary oblique shocks is less than the pressure rise across a single normal shock at the freestream Mach number.…”
Section: Oblique Crossing Shock Interactionmentioning
confidence: 99%